The Assessment of Different Dietary Selenium Resources on Reproductive Performance, Spawning Indicators, and Larval Production of Red Tilapia (Oreochromis mossambicus × O. niloticus) Broodfish - Mohammed A. E. Naiel; El-Sayed H. Eissa; Yasmin M. Abd El-Aziz; Saadea Saadony; Heba E. Abd Elnabi; Salah El-Sayed Sakr (Aquaculture Nutrition)
This trial aimed to investigate whether dietary selenium form influenced the reproductive performance of red tilapia broodfish. Four experimental broodstock diets were prepared employing two types of selenium. The first diet was free of additives and acted as the control diet. While the other three formulated diets were supplemented with conventional selenium sources (sodium selenite, Na2SeO3; 1 mg/kg), selenium nanoparticles (NPSe, 1 mg/kg), or a combination of them (0.5 mg Na2SeO3/kg + 0.5 mg NPSe/kg), respectively. Twelve cement ponds (each 24 m2) were subjected to fish brooder experimental groups. Each pond received six prespawning females (mean initial weight, 60.9 ± 0.4 g) and two males (mean weight 80.3 ± 0.8 g) of red tilapia. Each formulated diet was supplied to three broodfish cement ponds, and the reproductive traits of 18 adult female fish were monitored over 25 weeks. The findings showed that female fish fed NPSe-enriched diets had significantly higher viscera, liver, and gonad weight than other experimental groups. At the same time, the highest levels of LH, progesterone, and estradiol-17β, as well as the lowest levels of FSH, were detected in fish fed the NPSe diet, followed by those on the Na2SeO3 + NPSe and Na2SeO3 diets, respectively. Furthermore, the diameter, weight, and volume of eggs, as well as the number and weight of larvae in red tilapia brooder fish fed the various dietary selenium forms, increased markedly (P<0.001). Female red tilapia broodfish given selenium-based diets enhanced all spawning performance indicators (particularly total spawned egg per pond or fish and initial spawning interval) when compared to a control group fed an unsupplemented diet. Besides, as compared to other treatment groups, the spawning frequency of each female fish fed NPSe-supplemented diets (alone or in combination with Na2SeO3) was considerably (P<0.001) promoted. The fish group fed NPSe alone or mixed with Na2SeO3 had a well-developed stroma structure, many mature vitellogenic and postvitellogenic oocytes, and a remarkable intensity of mature spermatozoa in the testis. In conclusion, incorporating NPse into red tilapia broodstock diets might be a safe and efficient way to enhance reproductive function and fry production.